Stability of a 2-Dimensional Functional Equation in a Class of Vector Variable Functions - Bae Jae-Hyeong; Park Won-Gil (Journal of Inequalities and Applications, 2010)
We prove the Hyers-Ulam stability of a 2-dimensional quadratic functional equation in a class of vector variable functions in Banach modules over a unital -algebra.